Making Other Worlds Possible : Performing Diverse Economies - Gibson-Graham, J. K.; St. Martin, Kevin, 1962-; Roelvink, Gerda, 1978- (Book collections on Project MUSE., 2015)
Safri, Drew U; Robert Snyder, Island Institute; Karen Werner, Goddard College.